Strategi Peningkatan Nilai Akreditasi Institusi Perguruan Tinggi Dengan Menggunakan Quality Function Deployment (QFD) (Studi Kasus Di Institusi Politeknik) - Krisnaningsih, Erni (Journal Industrial Servicess, 2017)
Higher Education Institutions Accreditation value (AIPT) Reflecting the quality of the management of a university. The number of institutions with private universities in Indonesia are not yet accredited, the Polytechnic Piksi Input Attack seeks to increase the value of accreditation of Higher Education Institutions in which the current value of accreditation of universities Polytechnic Institute Piksi C. Input Attack is an increase in the value of accreditation Institutional Strategy colleges do using data from the assessment the assessor visitation BAN PT contained in Higher Education Institutional Accreditation Assessment consisting of grains assessment indicators. Based on the strategy for improving the quality of the value of accreditation by using a Service Quality (ServQual) to determine the value Gap for the assessment indicators AIPT, based on the value dimension of Service Quality (SERVQUAL) ranging from the largest to smallest is Tangible, responsivenes, empathy, Reliability  and Assurance. Quality function deployment (QFD) is a tool used to determine the needs and wants increase in value Accreditation Higher education, find a response innovative to those needs, improve processes to achieve maximum effectiveness. Based on House of quality (HOQ) can know the needs of consumers (Customer requirement), the Technical descriptors in response to consumer demand, which in turn acquired the value ranking and priority for each Technical Descriptors. Improvements are gradually against all the assessment indicators AIPT and reviuw against achievement of the strategy to increase the value of structured and scheduled AIPT expected to increase the value of accreditation visitation PT in the period to come.